A case report of portal vein thrombosis and common bile duct compression in the patient having pseudocyst of pancreas and its management by percutaneous trans-hepatic biliary drainage - Baldiwala, Aafrin S.; Chandnani, Rajesh G. (International Surgery Journal, 2021)
Pancreatitis is a systemic disease owing to release of inflammatory mediators and digestive enzymes. Acute pancreatitis is sudden inflammation of the pancreas. Alcohol and gallstones are main cause of acute pancreatitis. Chronic pancreatitis is the persistent inflammation and irreversible fibrosis associated with atrophy of pancreatic parenchyma. There are various complications associated with pancreatitis such as strictures, pancreatic necrosis, pseudo-cyst of pancreas, pancreato-cutaneous fistulas, venous thrombosis, arterial aneurysm in various arteries around pancreas etc. Common bile duct (CBD) strictures are a common complication in patients with advanced chronic pancreatitis and have a variable clinical presentation ranging from an incidental finding to overt jaundice and cholangitis. CBD strictures occur as a consequence of recurrent acute inflammatory episodes which may ultimately result in a periductal fibrotic stricture. CBD can be compressed as a result of extrinsic compression by large pseudocyst or aneurysm. The diagnosis is mostly made during investigations for abdominal pain but jaundice may be the initial clinical presentation. The jaundice is typically transient but may be recurrent with a small risk of secondary biliary cirrhosis in longstanding cases. Vascular complications in chronic pancreatitis are rare. Venous thrombosis is the most common complication of pancreatitis affecting venous system. It occurs as consequences of an inflammatory mass in head of pancreas, and splenic vein thrombosis occurs in association with chronic pancreatitis in 4-8% cases. Present case is a case of acute pancreatic collection in head of pancreas with aneurysmal small bleeding causing complete CBD compression and extensive venous thrombosis involving superior mesenteric vein, portal vein, splenic.